Réponses

2012-11-05T11:36:28+01:00

1-(4/12+3/12)
=12/12-7/12 
=5/12

1-(1/3+1/6+1/9)
=18/18-(6/18+3/18+2/18)
=18/18-11/18
=7/18

-4/3-(5/6-1/4)
=-16/12-(10/12-3/12)
=-16/12-7/12
=-23/12

1/5-(-1/15+3/25)+2/3
=15/75-(-5/75+9/75)+50/75
=65/75-4/75
=61/75 

2012-11-05T11:48:12+01:00

1-(1/3+1/4)=1-(4/12+3/12)=1-7/12=12/12-7/12=5/12

 

1-(1/3+1/6+1/9) -4/3-(5/6-1/4)=1-(6/18+3/18+2/18)-4/3-(10/12-3/12)

=1-11/18-4/3-7/12=36/36-22/36-48/36-21/36=-55/36

 

1/5-(-1/15+3/25)+2/3=1/5-(-5/75+9/75)+2/3=1/5-4/75+2/3=15/75-4/75+50/75=61/75